“Walking on eggshells”: a qualitative study on the effects of trauma and deployment in military couples - Henry, Stacey Blalock (Kansas State University, 2011)
The purpose of this qualitative study was to gain an in-depth understanding of the systemic effects of trauma, particularly war-related traumatic stress as a result of military deployments to Iraq and Afghanistan, in a sample of recent war veterans and their spouses. With recent military deployments and redeployments of soldiers, empirical and clinical research is needed to eliminate further deterioration and retraumatization caused by personal and interpersonal traumatization that can lead to severe PTSD and other trauma-related symptoms. Much of the research on previous wars focused on the individual trauma survivor overlooking the impact on the couple and family system. This study focused on explaining the systemic effects of trauma as it specifically impacts couple relational systems. By employing qualitative analysis, six couples (12 participants) were selected from the original data set of 45 couples (90 participants). Participants completed questionnaires and separate individual standardized open-ended interviews about their traumatic experiences. The interviews were transcribed, coded, and analyzed producing four themes: positive impact of deployment on the couple’s relationship, the negative impact of deployment on the couple’s relationship, soldiers’ war-related trauma, and issues of secrecy. Two groups were identified (high trauma/high relational satisfaction group and high trauma/low relational satisfaction group), based on the quantitative measures that were completed by all participants. Participants reported both war deployment related and non-deployment related traumatic experiences. Many participants reported feeling as though they restarted their relationship upon returning home, while some described feeling closer to their spouse at redeployment. Participants reported having a common worry of if the soldiers would return home alive, soldiers’ missing many life events (i.e., child birth, etc.), and soldiers’ worry about the safety and health of their spouses. An interesting finding was that some couples with high levels of trauma can maintain high levels of relational satisfaction when they have knowledge and understanding of each other’s trauma history and have open, on-going communication, while some couples with high levels of trauma tend to have low relational satisfaction due to limited communication about their trauma history. Strengths and limitations of the study, research implications, and clinical implications were discussed.
Keywords: Effects of trauma in couples; Military couples deployment; Psychology, Behavioral (0384)